2000
DOI: 10.1007/s004649900095
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous laparoscopic biliary and retrocolic gastric bypass in patients with unresectable carcinoma of the pancreas

Abstract: Simultaneous laparoscopic biliary and retrocolic gastric bypass is a safe and effective technique for the treatment of biliary and gastroduodenal obstruction in patients with unresectable pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 14 publications
(27 reference statements)
1
15
0
Order By: Relevance
“…Palliation for unresectable pancreatic cancer with obstruction of the biliary and/or the intestinal tract can be treated by endoscopic or surgical approaches. Previous research indicated that the surgical option of biliary and gastric bypass was superior to endoscopic intervention in terms of QoL, and rates of re-interventions and rehospitalization 6,7 . Palliative pancreaticoduodenectomy has been considered an acceptable alternative to bypass surgery 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Palliation for unresectable pancreatic cancer with obstruction of the biliary and/or the intestinal tract can be treated by endoscopic or surgical approaches. Previous research indicated that the surgical option of biliary and gastric bypass was superior to endoscopic intervention in terms of QoL, and rates of re-interventions and rehospitalization 6,7 . Palliative pancreaticoduodenectomy has been considered an acceptable alternative to bypass surgery 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In symptomatic patients with advanced pancreatic cancer, palliative procedures such as gastroenterostomy and biliary bypasses may be laparoscopically performed [11,19]. Pancreatic resection for lesions located in the tail and body of the pancreas does not require dissection from the great vessels or anastomosis between the pancreas and small bowel, and thus, may be more amenable to laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Experience with laparoscopic cholecystojejunostomy has largely accrued in the form of small single-centre cohort series [9][10][11][12][13][14] . Shimi et al [5] described laparoscopic cholecystojejunostomy in 5 patients with advanced carcinoma of the pancreas.…”
Section: Laparoscopic Cholecystoenterostomymentioning
confidence: 99%